Coastal accumulation of microplastic particles emitted from the Po River, Northern Italy: Comparing remote sensing and hydrodynamic modelling with in situ sample collections. (January 2019) - Atwood, Elizabeth C.; Falcieri, Francesco M.; Piehl, Sarah; Bochow, Mathias; Matthies, Michael; Franke, Jonas; Carniel, Sandro; Sclavo, Mauro; Laforsch, Christian; Siegert, Florian
Abstract: Microplastic research has mainly concentrated on open seas, while riverine plumes remain largely unexplored despite their hypothesized importance as a microplastic source to coastal waters. This work aimed to model coastal accumulation of microplastic particles (1–5 mm) emitted by the Po River over 1.5 years. We posit that river-induced microplastic accumulation on adjacent coasts can be predicted using (1) hydrodynamic-based and (2) remote sensing-based modelling. Model accumulation maps were validated against sampling at nine beaches, with sediment microplastic concentrations up to 78 particles/kg (dry weight). Hydrodynamic modelling revealed that discharged particle amount is only semi-coupled to beaching rates, which are strongly mouth dependent and occur within the first ten days. Remote sensing modelling was found to better capture river mouth relative strength, and accumulation patterns were found consistent with hydrodynamic modelling. This methodology lays groundwork for developing an operational monitoring system to assess microplastic pollution emitted by a major river. Graphical abstract: Unlabelled Image Highlights: Beach sediment microplastic concentrations up to 78.8 particles/kg dry weight Water sampling (max 84.1 particles/m 3 ) highest along outer plume and within river Daily river discharged microplastic particles only semi-coupled to beaching rates Microplastic beaching rate strongly river mouth dependent and occurs within 10 days Remote sensing exposure modelling validated against hydrodynamic accumulation model